Analysis of The Impact of Resources on Time Performance in an Oncology Hospital Project - Mohammad Syafei; Budi Susetyo (Eduvest - Journal of Universal Studies, 2026)
This study analyzes the influence of resource factors on project completion time performance in an oncology hospital construction project, which has high complexity due to specialized facilities such as radiotherapy rooms with radiation shielding requirements. The variables examined include equipment, work methods, materials, human resources, and financial factors. Data analysis employed a quantitative approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to examine structural relationships between latent variables. The inner model analysis yielded an R² value of 0.895, indicating that 89.5% of the variation in project time performance can be explained by the five factors. Direct hypothesis testing revealed that equipment is the most dominant variable (path coefficient 0.415; p-value 0.000), followed by work methods (0.258; p-value 0.012), materials (0.231; p-value 0.006), and human resources (0.142; p-value 0.014). Financial factors showed no significant effect (0.037; p-value 0.731). The study concludes that technical and operational factors—particularly equipment, work methods, materials, and human resources—have a greater influence on project delays than financial aspects. Recommended strategies include optimizing equipment management, strengthening efficient work methods, controlling material supply chains, and improving workforce competence and coordination to enhance time efficiency and project completion success.